Correlation of Nahwu Understanding to The Fast Process Memorizing Al-Qur'an Walisongo Islamic Boarding School Jombang - M Zainal Abidin Nur zain (SCHOOLAR: Social and Literature Study in Education, 2023)
This research was conducted at the Walisongo Islamic Boarding School in Jombang to find the relationship between the students' understanding of nahwu and the fast process of memorizing the Al-Qur'an. This research is very suitable for identifying the learning process of santri, including the relationships that influence the learning process or memory of santri at the age they are starting to reach adulthood. The method in this research was carried out through a quantitative approach using documentation studies. The data previously obtained was processed using descriptive analysis, percentage formulas, standard deviations and Contingency Coefficient Correlation analysis. In this case, the results of the research show that: first, this research is very suitable for identifying students' learning processes, including relationships that influence the learning process or memory of students at an early age. This research proves that there is a correlation between the understanding of nahwu possessed by students and the fast process of memorizing the Al-Qur'an at the Walisongo Islamic Boarding School in Jombang. The data that has been obtained is then processed using descriptive analysis, percentage formulas, standard deviations and Contingency Coefficient Correlation analysis. In this case, the results of the research show that: first, this research is very suitable for identifying students' memorization processes, including the relationships that influence students' memorization or memory. Second, the level of understanding of nahwu santri which is in the high category is 43% or as many as 13 santri, the medium category is 27% or as many as 8 santri, and the low category is 30% as many as 9 santri . Meanwhile, there are 8 students who memorized the Qur'an in the high category with a score > 70, there are 8 students in the medium category, there are 10 students who fall into the sufficient category with a score range of 56 to 69, and students in the poor category with a score < 55 there are 12 students.